IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS MICROSITE PADA PESERTA DIDIK KELAS V SD NEGERI 64 AMBON - Sarbunan, Saul Silvester Y.T.; Rachman, Gazali; Lestuny, Carolina (Universitas Pattimura, 2024)
Technological developments have had a big impact on creating interactive media in learning. Today's learning media is more varied, especially media-based learning microsites. The aim of this research is to determine the implementation of a media-based learning microsite in PPKn learning on the topic of Pancasila in my life, class V at SD Negeri 64 Ambon. This research also aims to make teachers more motivated in creating and using interesting, creative and interactive learning media. This type of research is qualitative with observation, interview and documentation methods. The sources for this research are students in class V of SD Negeri 64 Ambon. The existing data is in the form of behavior in implementing media-based learning microsites in Civics subjects with the topic Pancasila in my life. The analytical method used in this case is interactive analysis. The presentation of the results of data analysis in this article uses informal methods. Results of implementing media-based learning microsite The Civics class V subject at SD Negeri 64 Ambon went well, was conducive and interactive. There are several weaknesses that arise when learning takes place. However, the advantages of this implementation have more impact than the disadvantages. Monotonous learning that makes students bored can be overcome by implementing a media-based learning microsite as an interactive learning medium.